Obstacle in Elementary Education Classroom Management Barriers in Managing Elementary School Classrooms - Rizqiatin Rosa; Nur Annisa Istifarin (Academia Open, 2026)
General Background: Classroom management is central to the success of learning processes, particularly in elementary education where learners undergo social, emotional, and moral development. Specific Background: Managing classroom dynamics and sustaining student engagement are complex in primary schooling because rule recognition, peer interaction, and discipline formation are still developing. Knowledge Gap: Although classroom management strategies are widely discussed, research detailing contextual obstacles in primary education remains limited and often prioritizes solution-oriented training without sufficiently examining underlying causes of management failure. Aims: This study identifies and analyzes obstacles in elementary classroom management and formulates conceptual recommendations for a conducive, productive, and sustainable learning environment. Results: Using a descriptive qualitative library research approach, the study finds that obstacles are multidimensional, stemming from teacher-related conditions (e.g., authoritarian leadership, monotonous instruction, limited knowledge, weak teacher–student rapport), student-related conditions (e.g., inconsistent behavior, low task responsibility, rule-breaking), family environment (parenting styles shaping discipline and motivation), and learning facilities (limited space, overcrowding, inadequate learning media and tools). These conditions reduce learning quality and contribute to less conducive classroom situations. Novelty: The article consolidates a contextual, factor-based mapping of primary education classroom management obstacles and aligns them with categorized handling domains (teacher authority, school authority, and issues requiring wider stakeholder involvement). Implications: Preventive, corrective, and curative actions—supported by collaboration among teachers, schools, committees, and parents—are indicated as essential pathways for addressing obstacles and guiding policy and strategy formulation in elementary education. Highlights: Obstacles originate from teacher-related conditions, learner conduct, family environment, and school facilities. These obstacles contribute to less conducive learning situations and reduced learning quality. Handling pathways include preventive action, corrective action, curative action, and coordination with school committees and parents. Keywords: Classroom Management, Elementary Education, Teacher Factors, Student Behavior, Learning Facilities